Konflik Kebijakan Pertambangan Antara Pemerintah dan Masyarakat di Kabupaten Buton - MAHRUDIN, MAHRUDIN (Jurnal Studi Pemerintahan, 2010)
The aims of this research are to analysis and describe problems that become a conflict, the actor, andsource of conflict at nickel mining in Talaga Raya Buton Municipal. The methods of this research usedescription qualitative approach. Data collect instrument use observation, interview anddocumentation. Research's result shows that conflict can be happened if there are no communicationbetween mining corporation, societies, and government security person in the term of no payback ofland, plant which damage because of nickel mining.Beside, in policy formulation without involvesocieties. So that, it will become a conflict between corporation, societis and government security. Thisresearch recommended for government to make rule, which involve societies in formulation, so theinterest of all elements will involve and they will implement together.